LEMBAGA BISNIS DAN EKONOMI DALAM ISLAM - Hamdani Hamdani (Investama : Jurnal Ekonomi dan Bisnis, 2022)
Islam, as a religion of rahmatan lil Alamin, provides guidance to all human beings in various business and economic aspects. Since the time of the Prophet, there have been many business institutions that have provided solutions to the problems of people's lives, one of which is Baitul Maal wa Tamwil (BMT). BMT functioned as treasurer or business barn for Muslims in the past who were able to manage Islamic finance. Apart from BMT, other business institutions in Islam are sharia pawnshops and sharia investments. Islam strongly encourages Muslims to always be diligent in saving or investing, and Islam prohibits wasting money. Because Islam adheres to economic and business justice for the welfare of society, this study aims to look at the functions and roles of business and economics in Islam. Where business institutions are formed at the initiative of Muslims with the aim of eradicating monopolies in trade and distributing business fairly.